2016
DOI: 10.1007/s12576-016-0444-5
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of antioxidant expression during muscle atrophy induced by hindlimb suspension in mice

Abstract: Oxidative stress contributes to acceleration of muscle atrophy. However, it is still not completely understood what triggers the production of reactive oxygen species (ROS) during muscle atrophy. The objective of this study was to investigate redox balance during muscle atrophy. ROS generators and antioxidants were analyzed in atrophied soleus muscles after 2 weeks of hindlimb suspension (HLS) in mice. The HLS group showed an increase in lipid peroxidation, upregulated NOX1 and NOXO1, and downregulated mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Additionally, we identified the up-regulated transcripts Ddit4 and Eif4ebp1 ( Figure 3A), which have been previously implicated in protein synthesis during skeletal muscle atrophy [29,30]. We also found upregulation in the expression of the antioxidant genes Gpx3, Mt1, and Mt2 ( Figure 3A), which have been described with a role in muscle repair in atrophic conditions [31][32][33].…”
Section: Relevant Transcripts and Regulatory Pathways Associated Withsupporting
confidence: 52%
“…Additionally, we identified the up-regulated transcripts Ddit4 and Eif4ebp1 ( Figure 3A), which have been previously implicated in protein synthesis during skeletal muscle atrophy [29,30]. We also found upregulation in the expression of the antioxidant genes Gpx3, Mt1, and Mt2 ( Figure 3A), which have been described with a role in muscle repair in atrophic conditions [31][32][33].…”
Section: Relevant Transcripts and Regulatory Pathways Associated Withsupporting
confidence: 52%
“…ROS generating subunits (Nox1) were significantly elevated indicating ROS is increased during atrophy. Also, a decrease in the expression of antioxidants that scavenge ROS and a decrease in subunits of the mitochondrial complex 1 were observed, further indicating mitochondrial dysfunction associated with atrophy (Nuoc et al, 2016).…”
Section: Mitochondrial Dysfunction Associated With Atrophymentioning
confidence: 97%
“…Although there were no changes in elevated levels of non-heme iron, oxidative damage was decreased after reloading for seven and 14 days [ 112 ]. Mice were subjected to HLU for two weeks; the results suggested that imbalanced redox homeostasis occurred during muscle atrophy, due to the activation of NOX1, the deficiency of mitochondrial complex I, and the interference of antioxidants [ 113 ]. It has been well demonstrated that reduced protein synthesis and elevated protein degradation in muscle seems to be the major trigger in disuse muscle atrophy.…”
Section: Iron and Ros Signaling In Spaceflight-induced-bone Loss Amentioning
confidence: 99%